2020
DOI: 10.3991/ijim.v14i21.18475
|View full text |Cite
|
Sign up to set email alerts
|

Visualization of Learning and Memorizing Processes Using Mobile Devices: Mind Mapping and Charting

Abstract: <p class="0abstract">The purpose of the study is to test the effectiveness of visualization of learning and memorization in the educational process in higher educational institutions. The research was carried out in higher educational institution in the Russian Federation among 1-4-year students as well as teachers. The sample included 200 students and 35 teachers. The experiment consisted of three stages - introductory, experimental, and final. The initial assessment of students’ professional knowledge … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…Experience has shown that up-todate mobile devices can provide the opportunity for lectures, practical classes, and other types of training provided that participants are in different locations in the period of distance learning required by the Covid-19 pandemic [6]. It has become an alternative to face-to-face training during the Covid-19 pandemic [7].…”
Section: Introductionmentioning
confidence: 99%
“…Experience has shown that up-todate mobile devices can provide the opportunity for lectures, practical classes, and other types of training provided that participants are in different locations in the period of distance learning required by the Covid-19 pandemic [6]. It has become an alternative to face-to-face training during the Covid-19 pandemic [7].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to learning science, the mind mapping method is also appropriate for language learning (Serevina & Heluth, 2022;Su et al, 2022). Many benefits are obtained in the mind mapping method, namely (1) increasing the absorption of knowledge, (2) maximizing the working system of the brain, (3) lots of ideas and information that can be explained, (4) spurring creativity, and (5) developing divergent thinking skills and converge (Hidayat et al, 2020;Vorona et al, 2020). The contribution of this research also supports the cognitive learning theory by Jean Piaget that the learning process must maximize the working potential of the brain (Juwantara, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Students can also visualize problems using CMM. The method of visualizing and systematizing information for learning can enhance students' academic performance (Vorona-Slivinskaya et al, 2020). CMM facilitates the visualization of the connection between the main theme and problem branches (Hakim et al, 2020).…”
Section: The Combination Of Ricosre and Collaborative Mind Mapping In...mentioning
confidence: 99%